1995
DOI: 10.1111/j.1365-2958.1995.tb02352.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA bending introduced by the Pseudomonas putida LysR‐type regulator, CatR, at the plasmid‐borne pheBA and chromosomal catBC promoters

Abstract: The plasmid-borne pheBA operon of Pseudomonas putida strain PaW85 allows growth of the host cells on phenol. The promoter of this operon is activated by the chromosomally encoded LysR-type regulator CatR, in the presence of the inducer cis,cis-muconate. cis,cis-muconate is an intermediate of catechol degradation by the chromosomally encoded ortho or beta-ketoadipate pathway. The catBC operon encodes two enzymes of the beta-ketoadipate pathway and also requires CatR and cis,cis-muconate for its expression. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…Regulators similar to BenM include CatR and ClcR of Pseudomonas putida which regulate the catabolism of catechol͞phenol and 3-chlorocatechol, respectively (6)(7)(8). They are Class I transcriptional activators that contact a C-terminal region of the ␣-subunit of RNA polymerase (9).…”
mentioning
confidence: 99%
“…Regulators similar to BenM include CatR and ClcR of Pseudomonas putida which regulate the catabolism of catechol͞phenol and 3-chlorocatechol, respectively (6)(7)(8). They are Class I transcriptional activators that contact a C-terminal region of the ␣-subunit of RNA polymerase (9).…”
mentioning
confidence: 99%
“…CCM allows CatR to bind to a second site, the activation binding site (ABS) and to activate transcription from the promoter. Binding of CatR to the ABS of the catBCA or the pheBA promoter is cooperative, requiring the presence of an intact RBS (Kasak et al, 1993 ;Parsek et al, 1992Parsek et al, , 1995. Footprinting studies revealed that the ABS overlaps the k35 hexamer of the promoters (Chugani et al, 1997 ;Parsek et al, 1992Parsek et al, , 1995.…”
Section: Ipmentioning
confidence: 99%
“…A comparison of the nucleotide residues in the pheBA and catBCA promoters suggests that the two promoters are highly conserved and the DNase I protection patterns of CatR on these two promoter sequences are very similar (Chugani et al, 1997 ;Parsek et al, 1995) (Fig. 1b).…”
Section: Ipmentioning
confidence: 99%
See 2 more Smart Citations